Medial transport of the fibula using the Ilizarov device for reconstruction of a large defect of the tibia - Malik, Adnan Latif; Hanif, Muhammad (Journal of Fatima Jinnah Medical University, 2020)
Background: Large tibial defects are always a challenging to treat, especially those associated with soft tissue compromise and infection. There are different treatment options available for bridging such gaps. Therefore, current study undertakes to test Ilizarov technique for transport of fibula to establish its usefulness in bridging large tibial defects. Patients and Methods: This prospective case series was carried out from April 2013 to December 2016 at Orthopedic ward Lahore General Hospital in which 11 patients with large tibial defects having associated compromised soft tissue were treated by medial transport of fibula using Ilizarov external fixator. Results: Among total 11 patients, 63.6% were male while 36.4% were female. The mean age of the patients was 31.6 years. There were 45.5% patients reported with right side while 6 (54.5%) were reported with left side tibia with bone defect. Most of the patients (54.5%) had open fracture with bone loss while 45.5% patients had chronic osteomyelitis. Average time to union was 5.2 months. Average tibial defect size was 10.7 cm. Among them 72.7% patients regained normal walk. All patients had multiple previous surgeries on their limbs. Conclusion: Use of Ilizarov for medial transport of fibula is an effective procedure for reconstruction of large tibial defects especially in those patients who underwent multiple previous surgeries and with compromised soft tissue.